Symbols of power luxury textiles from Islamic lands, 7th-21st century - Mackie, Louise W. (Cleveland Museum of Art, 2015)
For centuries, luxury textiles were symbols of status, wealth and power at Islamic imperial courts from the Atlantic to the Indian Ocean, setting standards for beauty and fueling prosperous, urban economies. This book offers an unparalleled examination of Islamic luxury textiles, drawn from the Cleveland Museum of Art's exemplary collection as well as from museums on four continents. Leading scholar Louise W. Mackie offers a generous overview of the cultural significance of these textiles, as well as descriptions of primary motifs and patterns, and explanations of various techniques used in their production. With singular insight into distinctive artistic characteristics of wealthy dynasties and periods, the text - complemented by more than 450 sumptuous illustrations - pinpoints luxury textiles as a vital link between art, culture and history of the Islamic world. This book offers a much needed contribution to scholarship on both textiles and Islamic art, and paves the way for further study and appreciation of these objects.